Metabolic Reprogramming Regulates the Proliferative and Inflammatory Phenotype of Adventitial Fibroblasts in Pulmonary Hypertension Through the Transcriptional Corepressor C-Terminal Binding Protein-1. Issue 15 (11th October 2016) - Li, Min; Riddle, Suzette; Zhang, Hui; D'Alessandro, Angelo; Flockton, Amanda; Serkova, Natalie J.; Hansen, Kirk C.; Moldvan, Radu; McKeon, B. Alexandre; Frid, Maria; Kumar, Sushil; Li, Hong; et al.
Abstract : Background: Changes in metabolism have been suggested to contribute to the aberrant phenotype of vascular wall cells, including fibroblasts, in pulmonary hypertension (PH). Here, we test the hypothesis that metabolic reprogramming to aerobic glycolysis is a critical adaptation of fibroblasts in the hypertensive vessel wall that drives proliferative and proinflammatory activation through a mechanism involving increased activity of the NADH-sensitive transcriptional corepressor C-terminal binding protein 1 (CtBP1). Methods: RNA sequencing, quantitative polymerase chain reaction, 13 C–nuclear magnetic resonance, fluorescence-lifetime imaging, mass spectrometry–based metabolomics, and tracing experiments with U- 13 C-glucose were used to assess glycolytic reprogramming and to measure the NADH/NAD + ratio in bovine and human adventitial fibroblasts and mouse lung tissues. Immunohistochemistry was used to assess CtBP1 expression in the whole-lung tissues. CtBP1 siRNA and the pharmacological inhibitor 4-methylthio-2-oxobutyric acid (MTOB) were used to abrogate CtBP1 activity in cells and hypoxic mice. Results: We found that adventitial fibroblasts from calves with severe hypoxia-induced PH and humans with idiopathic pulmonary arterial hypertension (PH-Fibs) displayed aerobic glycolysis when cultured under normoxia, accompanied by increased free NADH and NADH/NAD + ratios. Expression of the NADH sensor CtBP1 was increased in vivo and in vitro in fibroblasts within the pulmonary adventitia of humans with idiopathic pulmonary arterial hypertension and animals with PH and cultured PH-Fibs, respectively. Decreasing NADH pharmacologically with MTOB or genetically blocking CtBP1 with siRNA upregulated the cyclin-dependent genes (p15 and p21) and proapoptotic regulators (NOXA and PERP), attenuated proliferation, corrected the glycolytic reprogramming phenotype of PH-Fibs, and augmented transcription of the anti-inflammatory gene HMOX1 . Chromatin immunoprecipitation analysis demonstrated that CtBP1 directly binds the HMOX1 promoter. Treatment of hypoxic mice with MTOB decreased glycolysis and expression of inflammatory genes, attenuated proliferation, and suppressed macrophage numbers and remodeling in the distal pulmonary vasculature. Conclusions: CtBP1 is a critical factor linking changes in cell metabolism to cell phenotype in hypoxic and other forms of PH and a therapeutic target. Abstract : Supplemental Digital Content is available in the text.